Peroxidase‐Like FeCoZn Triple‐Atom Catalyst‐Based Electronic Tongue for Colorimetric Discrimination of Food Preservatives. Issue 15 (4th January 2023) - Li, Heng; Sun, Mengru; Gu, Hongfei; Huang, Juan; Wang, Guo; Tan, Renjian; Wu, Rufen; Zhang, Xinyu; Liu, Shuhu; Zheng, Lirong; Chen, Wenxing; Chen, Zhengbo
Abstract: Recently, single‐atom catalysts are attracting much attention in sensor field due to their remarkable peroxidase‐ or oxidase‐like activities. Herein, peroxidase‐like FeCoZn triple‐atom catalyst supported on S‐ and N ‐doped carbon derived from ZIF‐8 (FeCoZn‐TAC/SNC) serves as a proof‐of‐concept nanozyme. In this paper, a dual‐channel nanozyme‐based colorimetric sensor array is presented for identifying seven preservatives in food. Further experiments reveal that the peroxidase‐like activity of the FeCoZn TAzyme enables it to catalyze the oxidation of 3, 3′, 5, 5′‐tetramethylbenzidine (TMB) and o‐phenylenediamine (OPD) in the presence of H2 O2, yielding the blue oxTMB and yellow oxOPD, respectively. However, food preservatives are adsorbed on the nanozyme surface through π–π stacking interaction and hydrogen bond, and the reduction in catalytic activity of FeCoZn TAzyme causes differential colorimetric signal variations, which provide unique "fingerprints" for each food preservative. Abstract : A dual‐channel colorimetric sensor array based on peroxidase‐like FeCoZn triple‐atom catalyst for discrimination of food preservatives is developed. The array's dual channels consist of two colorimetric reactions, i.e., FeCoZn‐catalyzed the reaction of OPD and H2 O2 and the reaction of TMB and H2 O2 .